2011
DOI: 10.3989/scimar.2011.75n1155
|View full text |Cite
|
Sign up to set email alerts
|

Trace metals (Cu, Zn, Cd and Pb) in juvenile fish from estuarine nurseries along the Portuguese coast

Abstract: SUMMARY: Organic and inorganic pollution can impact organisms directly and affect condition, growth and survival of juvenile fish which use estuaries as nurseries, and thereby affect marine adult populations quantitatively and qualitatively. Trace element contamination (Cu, Zn, Cd, Pb) in juveniles of commercial fish Solea solea, Solea senegalensis, Platichthys flesus, Diplodus vulgaris and Dicentrarchus labrax collected in putative nurseries of the main Portuguese estuaries (with diverse intensities and sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…For a given size, lower levels of metals were observed in the muscle tissues compared to other organs with distinct physiological functions and in particular the liver is often recommended for monitoring the metal contamination in aquatic environment. 49,51,52 The study of Vasconcelos et al 19 showed no significant differences in metal accumulation in flounder muscles among estuaries. The authors suggested that the limited time spent by the juveniles in the estuaries, estimated to be about three months, could explain both their relatively low levels of contamination in muscles and the lack of difference in metal accumulation among estuaries.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…For a given size, lower levels of metals were observed in the muscle tissues compared to other organs with distinct physiological functions and in particular the liver is often recommended for monitoring the metal contamination in aquatic environment. 49,51,52 The study of Vasconcelos et al 19 showed no significant differences in metal accumulation in flounder muscles among estuaries. The authors suggested that the limited time spent by the juveniles in the estuaries, estimated to be about three months, could explain both their relatively low levels of contamination in muscles and the lack of difference in metal accumulation among estuaries.…”
Section: Discussionmentioning
confidence: 93%
“…A recent study 19 has reported metal concentrations measured in the muscle of five fish species with an average length of 83.5 AE 7.0 mm for juvenile flounder. For the investigated metals, juvenile flounder from three Portuguese estuaries showed detectable levels for the two analysed essential metals (Cu and Zn) in muscle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results therefore provide valuable information about muscle contamination in these two species, especially for Al and Ti, for which very few data exist in the literature. To our knowledge, only one study so far has measured metal concentrations in the muscle of Diplodus juveniles in the wild, in D. vulgaris from six natural estuarine nursery sites spread along the Portuguese coast, and considered as slightly to moderately polluted (Vasconcelos et al, 2011). Muscle contamination levels for Cu and Zn in this work (of 2.1 mg.kg -1 dm and 28 mg.kg -1 dm on average, respectively) were close to those found for D. vulgaris in our study (Table 3), with the exception of the Cu concentrations observed in STM (2.0-8.9 mg.kg -1 dm).…”
Section: Environmental Contamination and Fish Contaminationmentioning
confidence: 99%
“…Yet, many coastal habitats under high anthropogenic influence, like most estuaries and coastal lagoons, have been shown to sustain important densities of juvenile fish with high growth rates (Beck et al, 2001;Franco et al, 2006;Gibson, 1994) and are, as such, listed as nursery habitats for many species. As recipients of industrial and domestic wastes, these systems are subjected to moderate to high pollution (Amara et al, 2007;Courrat et al, 2009;Vasconcelos et al, 2011), which does not seem to alter their nursery function.…”
Section: Introductionmentioning
confidence: 99%